Metronomic doses and drug schematic combination response tested within chambered coverslips for the treatment of breast cancer cells (JIMT-1) - Rosero, Gustavo (2022)
Low-dose metronomic (LDM) chemotherapy is an alternative to conventional chemotherapy and is the most frequently used approach in low dose chemotherapy regimens. The selection of patients, drug dosages, and dosing intervals in LDM is empirical. In this study, we systematically examined the schedule-dependent interaction of drugs on a breast cancer cell line (BCC) cultured in chambered coverslips. The LDM studies were combined with cell staining in order to better characterize different cell states and cell death modes, including caspase-dependent apoptosis, caspase-independent cell death and autophagy-dependent cell death. Microscope images were examined using the Fiji Trainable Weka Segmentation plugin to analyse cell area in 7500 images showing different modes of cell death. Paclitaxel combined with LDM chemotherapy demonstrated a reduction in the area covered by live cells. In contrast, there was an induction of high levels of cell death due to caspase-dependent apoptosis.